Assessment of Implementation Health Center Management Information System With Technology Acceptance Model (TAM ) Method And Spearman Rank Test In Jember Regional Health - Farlinda, Sustin (PROCEEDING IC-ITECHS 2014, 2014)
Public  Health  Center  (PHC)  Management  Information  System  (SIMPUS/SistemInformasi Manajemen Puskesmas) is one development of information technology in   health information systems that are managed by the health department. Department of Health in Indonesia to develop this SIMPUS since 2010. Examples of Jember District Health Office has implemented the SIMPUS in each health center so that the processing of data in health centers and report to the Department of Health can be efficient and effective. The number of PHC in Jember are 49 and have implemented SIMPUS  are  15 health centers.  SIMPUS The purpose of this study was to assess the implementation of the method SIMPUS Technology Acceptance Model (TAM) and test the variables of the TAM method influential or not in Jember Regional Health Center with statistical analysis using Spearman Rank test. The population in this study are 15 health centers,by sampling two respondents from each health center so that a sample of30 people at the responden. The results of this study indicate SIMPUS implementation assessment for Ease variable (Perceived Usefulness) is 85%, Variable Benefit (Perceived Ease Of Usefulness) is 89%. Usage and Attitude variables (Attitude Toward Using) is 87%. While the results of the analysis with Spearman Rank test the ease factor (perceived ease of use) related significantly to user attitudes Information System is the result of the calculation of the significance of 0,040. Benefit factors (perceived usefulness) significantly related to the attitude of the use of information system that is the result of the calculation of significance of 0.022, the benefit factor (perceived usefulness) related significantly to the convenience factor of Information Systems is the result of the calculation of significance of 0.000.